Social network sites as a moderating factor in E-Learning platform adoption: An extension - Medina, Cayetano; Rufin, Ramón (Lecture Notes in Computer Science, 2020)
The use of Social Network Sites (SNS), and the improvements gained from new technologies through e-learning platforms are two of the main topics that are currently discussed in the area of higher education. Acquiring a better understanding of e-Learning platform adoption requires the addition of new antecedents to prevailing models and an analysis of their interrelations with other information and communication technologies. Web 2.0 and SNS are of particular significance in this connection. This paper attempts to determine the validity of the antecedents posited by Chan et al. (2010) in the field of e-Learning and the moderating role that SNS use may play in platform adoption. The influence of awareness, self-efficacy, convenience and assistance as antecedents of the components of the adoption model is determined; it is further found that SNS use has a moderating effect on the relationship between the intention to use the platform and its posited antecedents.
Ponencia de la conferencia "9th European Conference on Technology Enhanced Learning, EC-TEL 2014; Graz; Austria; 16 September 2014 through 19 September 2014"
Keywords: adoption; assistance; awareness; convenience; e-learning; interaction effect; quasi-mediated relationships; selfefficacy; social network sites; UTAUT; Scopus(2); WOS(2)